Cisplatin plus gemcitabine versus paclitaxel plus gemcitabine as first-line therapy for metastatic triple-negative breast cancer (CBCSG006): a randomised, open-label, multicentre, phase 3 trial. Issue 4 (April 2015) - Hu, Xi-Chun; Zhang, Jian; Xu, Bing-He; Cai, Li; Ragaz, Joseph; Wang, Zhong-Hua; Wang, Bi-Yun; Teng, Yue-E; Tong, Zhong-Sheng; Pan, Yue-Yin; Yin, Yong-Mei; Wu, Chang-Ping; et al.
Summary Background Platinum chemotherapy has a role in the treatment of metastatic triple-negative breast cancer but its full potential has probably not yet been reached. We assessed whether a cisplatin plus gemcitabine regimen was non-inferior to or superior to paclitaxel plus gemcitabine as first-line therapy for patients with metastatic triple-negative breast cancer. Methods For this open-label, randomised, phase 3, hybrid-designed trial undertaken at 12 institutions or hospitals in China, we included Chinese patients aged 18–70 years with previously untreated, histologically confirmed metastatic triple-negative breast cancer, and an ECOG performance status of 0–1. These patients were randomly assigned (1:1) to receive either cisplatin plus gemcitabine (cisplatin 75 mg/m2 on day 1 and gemcitabine 1250 mg/m2 on days 1 and 8) or paclitaxel plus gemcitabine (paclitaxel 175 mg/m2 on day 1 and gemcitabine 1250 mg/m2 on days 1 and 8) given intravenously every 3 weeks for a maximum of eight cycles. Randomisation was done centrally via an interactive web response system using block randomisation with a size of eight, with no stratification factors. Patients and investigator were aware of group assignments. The primary endpoint was progression-free survival and analyses were based on all patients who received at least one dose of assigned treatment. The margin used to establish non-inferiority was 1·2. If non-inferiority of cisplatin plus gemcitabine compared with paclitaxel plus gemcitabine was achieved, we would then test for superiority. The trial is registered with ClinicalTrials.gov, number NCT01287624. Findings From Jan 14, 2011, to Nov 14, 2013, 240 patients were assessed for eligibility and randomly assigned to treatment (120 in the cisplatin plus gemcitabine group and 120 in the paclitaxel plus gemcitabine group). 236 patients received at least one dose of assigned chemotherapy and were included in the modified intention-to-treat analysis (118 per group). After a median follow-up of 16·3 months (IQR 14·4–26·8) in the cisplatin plus gemcitabine group and 15·9 months (10·7–25·4) in the paclitaxel plus gemcitabine group, the hazard ratio for progression-free survival was 0·692 (95% CI 0·523–0·915; pnon-inferiority<0·0001, psuperiority=0·009, thus cisplatin plus gemcitabine was both non-inferior to and superior to paclitaxel plus gemcitabine. Median progression-free survival was 7·73 months (95% CI 6·16–9·30) in the cisplatin plus gemcitabine group and 6·47 months (5·76–7·18) in the paclitaxel plus gemcitabine group. Grade 3 or 4 adverse events that differed significantly between the two groups included nausea (eight [7%] vs one [<1%]), vomiting (13 [11%] vs one [<1%]), musculoskeletal pain (none vs ten [8%]), anaemia (39 [33%] vs six [5%]), and thrombocytopenia (38 [32%] vs three [3%]), for the cisplatin plus gemcitabine compared with the paclitaxel plus gemcitabine groups, respectively. In addition, patients in the cisplatin plus gemcitabine group had significantly fewer events of grade 1–4 alopecia (12 [10%] vs 42 [36%]) and peripheral neuropathy (27 [23%] vs 60 [51%]), but more grade 1–4 anorexia (33 [28%] vs 10 [8%]), constipation (29 [25%] vs 11 [9%]), hypomagnesaemia (27 [23%] vs five [4%]), and hypokalaemia (10 [8%] vs two [2%]). Serious drug-related adverse events were seen in three patients in the paclitaxel plus gemcitabine group (interstitial pneumonia, anaphylaxis, and severe neutropenia) and four in the cisplatin plus gemcitabine group (pathological bone fracture, thrombocytopenia with subcutaneous haemorrhage, severe anaemia, and cardiogenic syncope). There were no treatment-related deaths. Interpretation Cisplatin plus gemcitabine could be an alternative or even the preferred first-line chemotherapy strategy for patients with metastatic triple-negative breast cancer. Funding Shanghai Natural Science Foundation.